TINGKAT PENGETAHUAN DAN SIKAP PERAWAT DENGAN TINDAKAN PENCEGAHAN INFEKSI LUKA OPERASI DI RUANG RAWAT BEDAH RSU KABUPATEN TANGERANG - eva marsepa; endra gunawan; uang musaeri (Jurnal Kesehatan, 2019)
Background : infection of the surgical wound is a nosocomial infection that will result in losses, especially for patients and health service providers. Nurses as implementers of health services that interact with patients for about 8 hours a day, potentially as a determining factor in the prevention of nosocomial infections, especially surgical wound infection. Research Objectives: to know the relation between knowledge level and attitude of nurse with prevention of surgical wound infection in surgical ward of Tangerang General Hospital. Research Method: correlative descriptive research with cross sectional approach. The sample of this research is all the nurses in surgical ward of Tangerang General Hospital as much as 45 samples by using total sample (total sampling). Data of knowledge and attitude were obtained by using validated and reliable questionnaires while prevention of wound infection was obtained based on observation. Data analysis used univariate and for bivariate with chi-square test. Results : of the 45 implementing nurses most of whom were 27 (60%) knowledgeable about prevention of surgical wound infection, 25 (55,6%) were positive (supportive) prevention of surgical wound infections, 30 (66, 7%) with good category to prevention of surgical wound infection. There is a correlation of knowledge with prevention of surgical wound infection with p value 0,023 (< alpha = 0,05). There is relation of attitude with prevention of surgical wound infection with p value 0,015 (< alpha = 0,05). Conclusions And Suggestions: there is relation of knowledge and attitude with prevention surgical wound infection. Hospital is expected to improve the knowledge and attitude of nurses and other officers in preventing nosocomial infection by involving several staff / nurses regularly to attend seminar, symposium, or training on prevention of nosocomial infection especially prevention of surgical wound infection.